Prevalence of gastroparesis symptoms and its associated factors among type 2 diabetes mellitus patients in West Bank in Palestine: a national cross-sectional study - Asad, Diya; Zreqat, Qusai; Idais, Shahd; Hussein, Bara'ah; Ayyad, Alaa; Hunjul, Marah; AbuGharbieh, Hamzeh M. I.; Neiroukh, Haroun; Zuhour, Areen; AbuKhalaf, Salsabeel; Al-Atrash, Nour; Alzughayyar, Roa; et al. (Frontiers in Medicine, 2025)
IntroductionDiabetic gastroparesis (DGP) is defined as delayed gastric emptying without any mechanical obstruction in diabetic patients.MethodsWe conducted a cross-sectional study using an Arabic-validated translated version of the Gastroparesis Cardinal Symptom Index (GCSI). A total of 3,542 diabetic patients were interviewed, of whom 91.6% were finally included in the analysis.ResultsDGP symptoms were present in 14.5% of the study population, of which 10.2% had a GCSI score of severe disease. Further analysis of individuals with GCSI scores≥1.9 (14.5%; 470) revealed that 50.8% of them visited a doctor at least once, and 18% had been hospitalized due to DGP symptoms. However, only nine patients (1.9%) were diagnosed with DGP. The most common symptoms were stomach fullness and early satiety. The binary regression model showed that DGP symptoms were more likely to occur in patients who had diabetes for >10 years and glycosylated hemoglobin >9. Furthermore, the model revealed that females were at a higher risk of developing DGP.DiscussionThis was the first study in Palestine on DGP, which showed that the condition is underdiagnosed. This is not only because of the unavailability of standard diagnostic methods but also due to the under appreciation of gastrointestinal complaints in diabetic patients.